(untitled) (Minerva, 2019)
In this article, we examine the presence of the Greek Anthology in the works of several Spanish poets of the last two decades. This presence is especially significant when dealing with the “Greek Eros” and the elegiac tone by which the concise and sententious nature offers an adequate form for the Greek epitaphs. In both cases, a previous knowledge of topics, motifs and forms is required for both the author and the reader.